Cyber Criminal Law Analysis on Electronic Medical Record Protection (Study at Mitra Medika Premier Hospital Medan) - Esti Budi Rahayu; Ismaidar Ismaidar (Fakultas Hukum Dehasen, 2026)
In today's digital era, the development of information technology has revolutionized various aspects of human life, including in the field of health. The use of electronic medical records in hospitals has become a common standard, allowing for more efficient storage of patient data and faster access for medical personnel. However, along with these advances, there have also been legal challenges, especially related to the protection of patients' personal data. The problems discussed are how the implications of cyber criminal law on the protection of electronic medical records in hospitals, what are the obstacles and obstacles in protecting electronic medical records at Mitra Medika Premier Medan Hospital and how cyber crime prevention efforts in protecting electronic medical records at Mitra Medika Premier Medan Hospital. The research used is empirical juridical using data collection methods through field research and library research. Literature Studies is obtained through reading, studying and studying books, laws and regulations, journals or data in the form of library materials while field studies are carried out by interview method. Some forms of violations that may occur in the management of electronic medical records at Mitra Medika Premier Medan Hospital are Unauthorized Access: When the login of an absent health worker is entrusted to another health worker to replace data entry and Data Collection: Patient data is used by unauthorized parties, for example photos of laboratory results. The efforts made by Mitra Medika Premier Medan Hospital in protecting health data include: Strengthening Technology Infrastructure: Implementing firewalls, antivirus, and data encryption, Routine Audits: Ensuring that the system runs according to security standards, Increasing Staff Awareness: Regular training related to data protection and Update/development of information technology systems, especially related to data security.